Enhancing Community Empowerment through Participatory Deployment of Portable Solar Panel Technology - Mega Novita; Imadudin Harjanto; Prasena Arisyanto; Wardatul Jannah; Mahyuddin Bin Arsat; Mohd Akhmal bin Muhamad Sidek (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Limited renewable energy literacy and community participation remain significant challenges to the sustainable adoption of solar energy technologies in rural areas. Although portable solar panel systems offer a practical solution for improving sustainable energy access, their long-term utilization is often constrained by insufficient community knowledge and technical capacity. This study evaluated the implementation of a portable solar panel system through a participatory community empowerment program in Jatirejo Village, Semarang Regency, Indonesia. A community service–based approach integrated educational sessions, hands-on training, practical demonstrations, and technology transfer to enhance participants' understanding and engagement in renewable energy utilization. Data were collected from 20 community members using structured pre- and post-program questionnaires, direct observations, and activity documentation and were analyzed descriptively. The proportion of participants who understood the basic functions of portable solar panel systems increased from 30% to 85%, while familiarity with system operation improved from 15% to 75%. Interest in renewable energy increased from 45% to 90%, and active participation during program activities increased from 25% to 80%. These findings indicate that the participatory approach strengthened local capacity and enhanced community acceptance of renewable energy technology. Integrating portable solar panel deployment with community empowerment activities provides an effective strategy for improving renewable energy literacy, promoting sustainable technology adoption, and strengthening community participation. The findings offer practical implications for community service initiatives, educational institutions, and local governments seeking to expand sustainable energy access and support the achievement of Sustainable Development Goal (SDG) 7 through participatory renewable energy programs.